The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1986
DOI: 10.1002/ajmg.1320250614
|View full text |Cite
|
Sign up to set email alerts
|

Fetal alcohol syndrome and DiGeorge anomaly. Critical ethanol exposure periods for craniofacial malformations as illustrated in an animal model

Abstract: Acute maternal ethanl (alcohol) administration induces different craniofacial anomalies in the offspring of experimental animals, depending on the gestational day of teratogen exposure. Previous studies in our laboratories have illustrated the sequence of developmental changes leading to the "typical" fetal alcohol syndrome (FAS) craniofacial phenotype which results from teratogen exposure during gastrulation. These facial features are accompanied by deficiencies in median forebrain derivatives. Ethanol terato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
80
0
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(84 citation statements)
references
References 22 publications
3
80
0
1
Order By: Relevance
“…Animal models have proved useful in evaluating outcomes of developmental exposure to alcohol (Driscoll, Streissguth, & Riley, 1990;Meyer, Kotch, & Riley, 1990a;1990b), and have illuminated the importance of blood alcohol profiles and patterns of exposure in determining neurobehavioral outcomes West et al, 1989). Experimental animal studies have identified relatively sharp temporal windows of vulnerability to alcohol-induced soft-tissue dysmorphology (Sulik, 1984;Sulik, Johnston, Daft, Russell, & Dehart, 1986). Animal models also provide the best means to investigate the role of developmental timing in determining the neurobehavioral outcomes (Clarren et al, 1990;.…”
Section: Introductionmentioning
confidence: 97%
“…Animal models have proved useful in evaluating outcomes of developmental exposure to alcohol (Driscoll, Streissguth, & Riley, 1990;Meyer, Kotch, & Riley, 1990a;1990b), and have illuminated the importance of blood alcohol profiles and patterns of exposure in determining neurobehavioral outcomes West et al, 1989). Experimental animal studies have identified relatively sharp temporal windows of vulnerability to alcohol-induced soft-tissue dysmorphology (Sulik, 1984;Sulik, Johnston, Daft, Russell, & Dehart, 1986). Animal models also provide the best means to investigate the role of developmental timing in determining the neurobehavioral outcomes (Clarren et al, 1990;.…”
Section: Introductionmentioning
confidence: 97%
“…In chick embryos, neural fold/NC ablation (Creazzo et al, 1998), Hox antisense experiments , teratogenic retinoic acid exposure (Broekhuizen et al, 1998) and haemodynamic perturbations (Hogers et al, 1999) have all caused 4 th and 6 th arch abnormalities. Similarly in mouse, teratogenic exposure to haloacetic acids (Hunter et al, 1996), ethanol (Sulik et al, 1986), and retinoic acid (RA) gives rise to arch abnormalities. Related or analogous pathological defects of the mouse 4 th and 6 th aortic arches and outflow tract are also seen when a large number of genes have been transgenically altered.…”
mentioning
confidence: 99%
“…This notion has been supported by animal studies. Single intraperitoneal injections of ethanol given to pregnant C57BL͞6J mice between E7 and E11 resulted in craniofacial abnormalities, including exencephaly and hypoplasia of the midfacial region and anomalies of the DiGeorge sequence (68)(69)(70). The onset of expression of msx2 in mouse embryos has been reported to occur as early as E9 and is still expressed as late as E17 (26).…”
Section: Discussionmentioning
confidence: 99%
“…The onset of expression of msx2 in mouse embryos has been reported to occur as early as E9 and is still expressed as late as E17 (26). Using closely spaced (4 hr) dual intraperitoneal injections of alcohol to mimic ''binge'' drinking, abnormalities with facial features similar to those noted in human FAS infants have been induced in fetal mice only when alcohol is present on or before E8 (31,(70)(71)(72)(73). By contrast, similar alcohol exposures at later stages of murine gestation could not induce murine craniofacial abnormalities.…”
Section: Discussionmentioning
confidence: 99%